Comprensión de futuros profesores de ciencia sobre aspectos epistémicos de la naturaleza de la ciencia en cuatro controversias de historia de la ciencia - Acevedo-Díaz, José Antonio; Aragón-Méndez, María del Mar; García-Carmona, Antonio (Revista Científica, 2018)
This article presents a global analysis of the results from four studies on pre-service secondary science teachers’ understanding of epistemic aspects of the nature of science (NOS). To this end, four controversies from the history of science (HOS) were used as teaching/learning context, and whose implementation in class was conducted through a critical and reflective approach. The analysis focused on determining the references that pre-service science teachers made in their responses to the different epistemic indicators established in the assessment rubrics, and the number of times that these were alluded. The findings obtained allow to conclude that, in general, the pre-service science teachers significantly improved their understanding on the influence of the epistemic aspects of NOS in the four controversies of HOS which were employed.